The Correlation Between Urban Development and Land Surface Temperature Change in Palembang City - Nadiya Tri Utami; Bitta Pigawati (Geoplanning: Journal of Geomatics and Planning, 2022)
Palembang city has experienced an increase in its population. Population growth results in an increase in activities which enlarge the built-up areas. The increase of built-up areas is one of the indicators of urban growth. The increase in built-up areas is inversely proportional to the vegetation area. Reduced vegetation area might cause an increase in land surface temperature. The aim of the study was to analyze the correlation between urban growth and changes in land surface temperature in Palembang City using descriptive quantitative method and spatial analysis on the data obtained from remote sensing images. The result shows that in 1998-2018, Palembang City has developed to the north (Sukarami District) and to the west (Ilir Barat I District). There has been an increase in the temperature, documented as 2.12°C. There is a correlation between urban growth and changes in land surface temperature in Palembang City